2012
DOI: 10.4236/nm.2012.31002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Relationships among Facets of Alexithymia and BDNF- and Dopamine-Related Polymorphisms

Abstract: Alexithymia refers to a cluster of emotion-related deficits such as difficulty attending to and identifying one's feelings. Although not a diagnosable psychiatric condition, alexithymia is considered a personality risk factor for multiple pathologies, including somatoform, substance use, eating, and mood disorders. Evidence suggests heritability, but few studies have examined the influence of specific genes on alexithymic traits. Candidate genes explored thus far include those involved in modulation of brain-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In fact, the Reinforcement Sensitivity Theory provides a framework for a neurobehavioral etiology of anxiety, or an explanation for how anxiety-related behaviors are linked to biological systems of punishment and reward (Gray 1970, 1976; Corr 2004; Gray and McNaughton 2000). Specifically, allelic variation for dopamine as a genetic moderator both provides support for individual differences in expressions of anxious behavior (Freitas-Ferrari et al 2010; Koven and Carr 2012; Schneier et al 2000) and a potential illustration of how genes confer vulnerability to environmental factors like exposure to social situations (Belsky and Pluess 2009). …”
Section: Biological Bases For Links Between Social Anxiety Symptoms Amentioning
confidence: 99%
“…In fact, the Reinforcement Sensitivity Theory provides a framework for a neurobehavioral etiology of anxiety, or an explanation for how anxiety-related behaviors are linked to biological systems of punishment and reward (Gray 1970, 1976; Corr 2004; Gray and McNaughton 2000). Specifically, allelic variation for dopamine as a genetic moderator both provides support for individual differences in expressions of anxious behavior (Freitas-Ferrari et al 2010; Koven and Carr 2012; Schneier et al 2000) and a potential illustration of how genes confer vulnerability to environmental factors like exposure to social situations (Belsky and Pluess 2009). …”
Section: Biological Bases For Links Between Social Anxiety Symptoms Amentioning
confidence: 99%
“…In another study, participants with the homozygous Val66Val genotype showed raised activity of the BDNF protein, in conjunction with reduced expression of the DRD2 gene seen in the DRD2 Taq1A genotype, leading to raised concentrations of dopamine [ 66 ]. Extreme dopamine concentrations, either too low or too high, are thought to disrupt cognitive function [ 67 ].…”
Section: Physiological Genetics/genomics In Aggressive Behaviour and ...mentioning
confidence: 99%